Kosmopolitanisme dalam Sejarah Relasi Aceh-Turki: Peran Keluarga Attahashi Di Kenegerian Sungai Iyu, Aceh Tamiang, Aceh - Madhan Anis; Aulia Rahman; Zulkifli Zulkifli; Okhaifi Prasetyo; Bukhari Bukhari; Guntur Arie Wibowo (Publikasi Berkala Pendidikan Ilmu Sosial, 2025)
This paper analyzes cosmopolitanism in the relations between Aceh and Turkey. Aceh has a rich and complex history of cosmopolitanism, one of which is its relationship with Turkey. This research aims to analyze the dynamics of cosmopolitanism in the context of the relationship between Turkey and Aceh, focusing on the Kenegerian Sungai Iyu and the significant role of the Attahashi family in the cosmopolitan relations in Sungai Iyu. This study employs a qualitative approach. Data were obtained through literature review, analysis of historical documents, and interviews with informants. The findings indicate that the relationship between Aceh and Turkey has had a significant influence on cosmopolitanism in Aceh. In the Kenegerian Sungai Iyu, the Attahashi family serves as a cultural bridge between Turkey and Aceh. Cosmopolitanism plays a crucial role in facilitating cultural exchange, mutual understanding, and cooperation between the people of Aceh and Turkey. Additionally, this relationship contributes to historical awareness in Aceh, enabling the local community to understand cosmopolitanism in the historical relations between Aceh and Turkey. Cosmopolitanism in the Aceh-Turkey relations in Sungai Iyu has produced collective memory through shared experiences in the past, shaping a narrative in the present that is passed down from generation to generation. This collective memory strengthens Aceh's cultural and historical identity and enriches the collective awareness of the Acehnese people about cosmopolitanism through the significant role of the Attahashi family. This paper contributes to the understanding of the importance of strengthening historical awareness through the historical narrative of the Attahashi family in Sungai Iyu.